Decolonizing memory : Algeria and the politics of testimony - Jarvis, Jill, 1979- (Duke University Press, 2021)
"Decolonizing Memory argues that writers and artists have played an important role in cultivating historical memory and nurturing political resistance in Algeria, and shows that the magnitude of the violence exercised by the French to colonize and occupy Algeria is such that only aesthetic works, in particular literature, have been able to register its enduring effects. Through readings of French and Arabic texts by writers including Zahia Rahmani, Yamina Mechakra, Waciny Laredj, Fadhma Aíth Mansour Amrouche, Frantz Fanon, Assia Djebar, and Samira Negrouche, the book centers Algeria as an important nexus of aesthetic creation and theoretical contestation. Its argument foregrounds the impasses and disjunctions brought to light by this constellation of literary texts to demonstrate how Algerian writers have transformed the genre of testimony in ways that both defy imposed linguistic partitions and dispute the authority of the state to be the ultimate arbiter of justice"--